Information literacy education : a process approach : professionalising the pedagogical role of academic libraries - Torras, Maria-Carme.; Saetre, Tove Pemmer, 1945- (Oxford : Chandos Pub., 2009)
This work helps information professionals design, carry out and evaluate a user education programme in information literacy for their higher education institute. The book puts forward a student-, a subject- and a learning-centred approach to user education.
Introduction -- An educational platform for information literacy -- Designing process-oriented information literacy education : the library practitioner as a professional and autonomous educator -- Facilitating the student's research process : the academic librarian as a supervisor -- Conclusions.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Library orientation for college students; Information services -- User education